Prospects for development of an effective Lyme disease vaccine - Herding, Emily J. (My University, 2016)
Lyme disease is the most prevalent tick-borne disease in the world, and the annual number of cases continues to increase. By this measure, a vaccine to prevent the illness would be valuable. However, the first commercial attempt at a human Lyme disease vaccine failed to adequately protect people for an extended period of time, and also caused serious side effects in a small population of recipients. Though many different vaccine formulations have been proposed and evaluated since then, none have yielded results sufficient to warrant progression to clinical trials. This review provides historical perspective of early efforts and discusses current strategies that may ultimately prove more effective at providing vaccine-induced antibody-mediated protection.
Keywords: Lyme disease--treatment; Lyme disease--diagnosis; Biology